Criminal Liability for Teachers Perpetrating the Rapes of Their Students: Child Protection Law Perspective - Mega Agrianty, Firly; Dewi, Sartika; Abas, Muhammad (UNES Law Review, 2024)
Rape is an act of sexual violence that forces someone into sexual relations, including those between a husband and wife. According to records from the Federation of Indonesian Teachers' Unions (FSGI), from the beginning of the year until May 2023, 31.08% of sexual violence cases against minors involved teachers. This study, using Normative Juridical research, examines the criminal liability of teachers who rape students and the judicial considerations in Decision Number: 156/Pid.Sus/2020/PN.Pkb. Findings indicate that teachers violating Article 81 paragraphs (1) and (3) are subject to criminal sanctions, including a minimum prison sentence of 5 years and a maximum of 15 years, as well as a fine of IDR 5,000,000,000.00 (five billion rupiah). Additionally, one-third of the principal penalty may be added. In the referenced case, Decision Number: 156/Pid.Sus/2020/PN.Pkb, the defendant received a sentence of 6 years in prison and a fine of IDR 10,000,000.00 (ten million rupiah). Failure to pay the fine would result in an additional 3-month prison term. Given the damage to the reputation of teachers, the panel of judges should have the authority to impose further punitive measures, such as publicizing the perpetrator's identity through print and social media. It is hoped that such measures will create a deterrent effect, discouraging similar offenses in the future.